Nilai-Nilai Manajemen dalam Al-Qur'an dan Implementasinya dalam Pendidikan Islam: Kajian Tafsir Al-Misbah - Mulyanah Mulyanah; Ade Budi; Ismail Ismail (Tadabbur: Jurnal Integrasi Keilmuan, 2026)
This study aims to identify and analyze the management values contained in the Qur’an based on the study of Tafsir Al-Misbah by M. Quraish Shihab and to examine their relevance in the implementation of Islamic education management. This research employs a qualitative approach using a library research method through content analysis of Qur’anic verses and interpretations found in Tafsir Al-Misbah. This study focuses on management values including planning, organizing, leading, controlling, responsibility, and decision-making based on Islamic values. The results show that the Qur’an contains management principles that emphasize order, trustworthiness, justice, consultation (shura), and responsibility in managing various activities, including education. Tafsir Al-Misbah provides a contextual understanding that management values in the Qur’an are not only related to organizational management in general but also serve as a foundation for developing an effective, character-based Islamic education system oriented toward the formation of morally upright individuals. The implementation of these values in Islamic education can be realized through the management of educational institutions that integrate spiritual, moral, and professional aspects in the processes of planning, implementation, and evaluation. This study demonstrates that management concepts based on Qur’anic values have strong relevance in addressing the needs of contemporary Islamic education management.